Challenges in the Diagnosis and Management of Intracranial Abscess in Developing Countries: A Retrospective Study from a Tertiary Hospital in Indonesia - Imron, Akhmad; Turbawaty, Dewi Kartika; Sumargo, Sheila; Ardisasmita, Mulya Nurmansyah (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Despite progressive development of antibiotics and surgical approaches, outcomes in patients with intracranial abscess remained far from ideal. This paper aimed to describe challenges in the diagnosis and treatment of intracranial abscess in developing countries based on study from a tertiary hospital in Indonesia. A retrospective study was performed and included patients who were suspected of intracranial abscess at a tertiary referral hospital in Indonesia between January 1, 2012 and January 1, 2020. Clinical, radiological and laboratory characteristics were analyzed. Two-hundred-and-seventy-seven patients were initially enrolled. Age (p = 0.001), GCS at admission (p = 0.009), comorbidity with hypoalbuminemia (p = 0.003) and hydrocephalus (p = 0.009) are significantly associated with patients’ GCS when discharged.  Results from culture and resistance tests could only be retrieved from 66 patients, with 33 (50%) obtained negative results, while the other 33 (50%) results were positive, consisted of 20 (60.6%) were of gram-negative bacteria and 13 (39.4%) were of gram-positive bacteria. Treatments that are directed to hypoalbuminemia and hydrocephalus should also be prioritized when any of these comorbidities exist.